2011
DOI: 10.1007/s13142-011-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

The many faces of translational research: a tale of two studies

Abstract: Translational research can take many forms: bench to bedside, across cultural groups, across geographical boundaries, among others. This case study will share how we addressed all three “translational” issues using two evidence-based studies (USA, Zambia) to illustrate these “roads less traveled.” Our implementation and dissemination efforts were anchored by the “train the trainer” strategy, and the Glasgow RE-AIM model provided programmatic guideposts and direction. Keeping all stakeholders (scientific, commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…based research program was implemented and evaluated in five urban community health centers (CHCs) in Miami, New York City (NY), and Northern New Jersey (NJ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…based research program was implemented and evaluated in five urban community health centers (CHCs) in Miami, New York City (NY), and Northern New Jersey (NJ) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several publications from three federally funded studies conducted by UMMSM and CDN over a 10-year period confirmed the evidence base of the program [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 91%
“…The SMART/EST (Stress Management And Relaxation Training/Emotional Supportive Therapy) Women's Project (SWP) is an evidence-based behavioral intervention designed to enhance the overall quality of life and health status of culturally diverse, disadvantaged women living with HIV/AIDS [3,4] Policy: Support in the form of government funding for community health center training can maximize the success, impact, and scope of translation research in health-care settings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations